Pollinator Deficits, Food Consumption, and Consequences for Human Health: A Modeling Study - Smith, Matthew R. (2022)
Fil: Smith, Matthew R. Harvard T.H. Chan School of Public Health. Department of Environmental Health. Estados Unidos.